Laser indicated occlusal plane device: A novel technique for occlusal plane orientation - Keerthika Natarajan; Murugesan Krishnan; Suganya Srinivasan; Gowtham Venkat; Muthukumar Balasubramanian (Wolters Kluwer Medknow Publications, 2023)
Parallelism to the ala-tragus line is commonly used as a guide for the orientation of the occlusal plane with the help of a fox plane. The accuracy of parallelism is affected by improper judgment or patient movement. This report describes a method with a modified fox plane that aids in occlusal plane determination. The device is placed in the patient's mouth with the maxillary occlusal rim to determine parallelism to the ala-tragus line and interpupillary line. The adjustments are made until the laser light on the device runs parallel to the ala-tragus line, and the spirit bubble is centered between the lines of the tube. This technique facilitates direct visualization of parallelism, thereby avoiding parallax errors.